Transformasi Ekonomi Keluarga melalui Peningkatan Minat Wirausaha Ibu-Ibu di Desa Tambakbaya - Chintia Fitriani (Universitas Negeri Gorontalo, 2026)
This community service activity aims to increase the entrepreneurial interest and capacity of PKK women in Tambakbaya Village. Key issues include low entrepreneurial interest, limited use of social media, and poor financial management. The methods used included outreach, training, technology implementation, and mentoring. Results showed significant improvement: 80% of participants were able to develop business plans, 70% utilized social media, and 80% maintained financial records. This program is effective in increasing family economic independence.